Pressureless sintering of highly transparent AlON ceramics with CaCO3 doping. (December 2018) - Shan, Yingchun; Sun, Xiannian; Ren, Binglin; Wu, Haokai; Wei, Xialu; Olevsky, Eugene A.; Xu, Jiujun; Li, Jiangtao
Abstract: Employing CaCO3 as sintering additive, highly transparent aluminum oxynitride (AlON) ceramics were pressurelessly fabricated from AlON powder at 1870 °C during150 min. The transmittance of the AlON doped with 0.3–0.4 wt% CaCO3 is up to 83–85% at ~3700 nm for 2 mm thickness samples, and their transmittances are consistently higher than that of the AlON doped with the ideal amount of Y2 O3 at wavelength ranging from 200 nm to 6000 nm. The AlON doped with CaCO3 exhibits the transmittance of 71% at 4800 nm (typical band for infrared targeting), which is higher by 6% than that of the doped Y2 O3 . Graphical abstract: Unlabelled Image